Experimental and predictive evaluation of mechanical properties of kenaf-polypropylene fibre-reinforced concrete using response surface methodology - Ja'e I.A.; Salih A.R.; Syamsir A.; Min T.H.; Itam Z.; Amaechi C.V.; Anggraini V.; Sridhar J. (Elsevier Ltd, 2024)
Fibre-reinforced concrete (FRC) is an emerging construction material. However, improving its mechanical properties using sustainable materials remains a concern. In this paper, a combination of experimental and numerical techniques is applied to investigate the combined influence of kenaf (K) and polypropylene fibre (PPF) on the mechanical properties of KPPFRC. The optimal design component of Response Surface Methodology was utilised with combined fibre content between 0.5% and 2%. The results show a general increase in the mechanical properties with KF being the main contributing factor, and corresponding decreases in all responses with the increase in PPF. Nonetheless, the predicted optimal volume fraction of 1.5% consisting of 1.0 kg kF and 0.51 kg PPF gives a 100%, 174% and 100% rise in compressive, split tensile, and flexural strength respectively compared to the control sample. Hence, these optimal proportions of KF and PPF can be utilised as an eco-friendly sustainable material in concrete. 2023 The Authors